O PIBID e a formação continuada de professores de ciências biológicas : contribuições para a prática docente - Santos, Márcia Zschornack Marlow (2016)
The present dissertation aims to approach the ongoing development of teachers and presents the findings of a survey consisting of 14 public school teachers in the Basic Education who act as supervisors of a Biology subproject in the Institutional Scholarship Program for Beginning Teachers (PIBID) in seven Higher Education Institutions of Rio Grande do Sul (RS). The purpose of this paper is to understand the impacts of the Institutional Scholarship Program for Beginning Teachers of the Biology subproject from different Higher Education Institutions for the ongoing development of the supervising teachers who work in the Basic Education schools in Rio Grande do Sul. In order to deepen the understanding about the contributions of PIBID to the ongoing development of teachers, an investigation of the teachers’ perceptions from different mesoregions of the State has been proposed. According to the criteria set by the Brazilian Institute of Geography and Statistics (IBGE), Rio Grande do Sul (RS) is divided into seven mesoregions (Mid-Western; Mid-Eastern; Metropolitan area of Porto Alegre; Northeast; Northwest; Southeast; South-West), from where the subjects of this survey were taken. For this purpose, a Higher Education Institution in each region was chosen as a sample. The data were collected by means of semi-structured recorded interviews and transcribed accurately by the researcher and analyzed through Discursive Textual Analysis. As the results of the analysis, categories that show an encouraging overview regarding the positive aspects that the program may offer to the ongoing development of teachers came out, especially with regard to the supervisors who work directly with the program. The engagement with the PIBID proposals renew the interest and affection for teaching. According to the teachers’ accounts, it is possible to observe significant changes in their teaching practice. From the activities carried out and developed in partnership with the scholars who supervise, we could notice that they adopted a more reflective attitude, reconsidering some perceptions and conceptions regarding their teaching performance. Therefore, from their personal accounts, it is possible to realize that the adoption of new methodologies and practices have become part of their teaching actions.